Inflammatory changes after cryosurgery-induced necrosis in human melanoma xenografted in nude mice - Gazzaniga, Silvina (2001)
There is growing evidence that necrosis, instead of apoptosis, could act as a natural adjuvant, which could activate an immune response. In this work we have investigated if induction of tumor necrosis could trigger the affluence of inflammatory cells at the tumor site, and thus induce an immune response. For this purpose, a liquid N 2 spray was applied on human melanoma (IIB-MEL-J cell line) xenografted in nude mice and 24 h later some mice received intratumorally a single 500 U dose of recombinant murine granulocyte macrophage-colony-stimulating factor. 77–100% of the tumor mass underwent necrosis. Congestion, edema, and endothelial cell activation were the first noticeable events. A quick infiltrative response of polymorphonuclear leukocytes around the tumor was detected 24 h after liquid N 2 application, peaking at day 3. Massive macrophage recruitment was observed since day 3. An early intratumoral infiltration with inflammatory cells was only detected in the group that received recombinant murine granulocyte macrophage- colony-stimulating factor after necrosis induction by liquid N 2. Coexisting DEC 205- and F4/80-positive cells increased in number, and their localization was predominantly peritumoral after necrosis. Antibody response was only detected in the groups with tumor-induced necrosis. Our results suggest that cryosurgery-induced necrosis could be a useful model to analyze the interaction among necrosis, inflammation, and the generation of an immune response.